The impact of sarcopenia and sarcopenic obesity on survival in children with Ewing sarcoma and osteosarcoma - BUĞDAYCI, ONUR (My University, 2023)
Abstract Background Sarcopenia is an indicator of negative outcomes in many diseases in adults. Reports indicate this might also be true in children. Objective To evaluate the efect of sarcopenia and sarcopenic obesity on event-free survival (EFS) and overall survival (OS) in children with Ewing sarcoma and osteosarcoma. Materials and methods We retrospectively measured total muscle areas of the pectoralis, paraspinal (T12 level) and psoas (L4 level) muscles and total abdominal muscle area (L3 level) on computed tomography images in 60 children diagnosed with either Ewing sarcoma (n=34) or osteosarcoma (n=26). Skeletal muscle indices (SMI) were calculated by normalizing muscle area to patient height. Vertebral morphologic parameters of T12 and L4 vertebrae were measured and correlated to patient height to use as a substitute in cases of missing height data (SMIT12 and SMIL4). We calculated sarcopenic obesity index by dividing SMI by body mass index. We subdivided children into two groups according to the median value of each parameter and assessed the diferences in survival between the groups. Results No skeletal muscle index or sarcopenic obesity index parameter signifcantly afected event-free or overall survival in the total group analysis. In the non-metastatic group, higher values of SMI–paraspinal and SMIT12–psoas were correlated with longer event-free survival and no patient died in this group. Boys and children in the metastatic group with higher SMIT12–paraspinal values had signifcantly longer event-free survival and both event-free and overall survival, respectively. Conclusion Although some parameters were correlated with event-free and overall survival, neither sarcopenia nor sarcopenic obesity were reliably associated with survival in children with Ewing sarcoma or osteosarcoma.
Keywords: Adolescent · Children · Computed tomography · Ewing sarcoma · Mortality · Obesity · Osteosarcoma · Sarcopenia